Mapping of base cation deposition in the Nordic countries - Persson, Christer (SMHI - Swedish Meteorological and Hydrological Institute, 2019)
Base cation deposition from the atmosphere provides, together with weathering, ions for neutralising acidity and, after sufficient reductions of acidifying deposition, a source for replenishing lost base cation pools. The present dataset is a mapping of base cations over the Nordic countries and was performed using the data assimilation part of the SMHI MATCH-model as of 2003 (optimum interpolation) with a grid spacing of 11km. The mapping was based on monitoring data for concentrations of base cations in air and precipitation in the Nordic and surrounding countries. For a detailed description of the methodology the reader is refered to Lövblad et al., 2003, pp7-14.

Datamaterialet består av en kartläggning av baskatjoner över de nordiska länderna och genomfördes med hjälp av dataassimileringsdelen av MATCH-modellen, med en upplösning på 11x11 meter. Kartläggningen baserades på övervakningsdata för koncentrationer av baskatjoner i luft och nederbörd i de nordiska och omgivande länderna. (MATCH är en avancerad datormodell som utvecklats på SMHI). En detaljerad beskrivning av metoden finns i Lövblad et al., 2003, sid 7-14.

För mer information se engelska sidan på https://snd.gu.se/en/catalogue/study/ECDS0075.
Mapping of base cation deposition in the Nordic countries
Keywords: atmospheric precipitation; atmosfäriskt nedfall; base (chemical); bas; Chemical Sciences; Kemi; Environmental Sciences; Miljövetenskap; Geoscientific Information; Geovetenskap; Environment; Miljö